The main consequences of continued illegal, unreported, and unregulated (IUU) fishing within Indonesian waters for maritime security actors and coastal communities (Research, Society and Development, 2020)
Illegal, Unreported and Unregulated Fishing is known as a global serious threat and become International major issues. Indonesia, as one of the biggest archipelago countries and Mega Biodiversity that has rich, various, and potential marine resources has succeeded in attracting domestic fisheries and foreign fisheries to commit Illegal, Unreported and Unregulated Fishing (IUU Fishing) practices. This research aims to understand the phenomenon of Illegal, Unreported and Unregulated Fishing in Indonesia and to understand the consequences of IUU Fishing practices to the coastal community and the maritime security state actors. This research finds that IUU Fishing practices have significant and negative impact towards Coastal communities on Economic, Environmental, and Social aspect. Furthermore, IUU Fishing practices has also significant and negative impact on the integrity of Maritime Security State Actors in protecting Indonesian waters.